Brand image benefits and halal destination loyalty: Are they truly linked? - Suddin Lada; Haneffa Muchlis Gazali; Mohd Nasir Samsulbahri; Rahida Abd. Rahman; Mohamad Isa Abdul Jalil; Tamrin Amboala (AnKa Publisher, 2020)
The HALAL tourism is flourishing in its own right as an industry, where Malaysia is the world's leading Halal industry with Halal tourism destination making a significant contribution to overall economic growth. However, to secure this reputable image Malaysia has to build a strong brand image groundwork for future sustainability. By obtaining a combination of brand image benefits and destination loyalty model, this study, therefore, aims to examine whether there is a significant relationship between brand image benefits (i.e. symbolic, functional, social, and experiential benefits) and destination loyalty among tourists visiting Malaysia as a brand of Halal tourism destination. A self-administered questionnaire was used to gather information from 300 selected respondents and analyzed it using Smart PLS. Results revealed that symbolic, functional, and experiential benefits have a significant relationship with destination loyalty among tourists visiting Malaysia. The theoretical and practical implications of the results are discussed and the future improvement of the research is suggested.